A Case of Severe Plasmodium falciparum Malaria Co-Infected with HIV Improved with Exchange Transfusion - Sağmak Tartar, Ayşe; Akbulut, Ayhan; Gökmen Sevindik, Ömür; Akbulut, Hatice Handan; Demirdağ, Kutbeddin (My University, 2017)
In our country, within years, despite a dramatic drop in the number of patients with malaria, a dramatic increase in the number of patients with import malaria is noteworthy. A 32-year-old male patient presented with fever, shivering, malaise, and loss of appetite. He had travelled to West Africa. Laboratory findings were as follows: hemoglobin: 8.8 g/dL and anti-HIV: positive. Microscopic examinations of thin blood smears and thick blood preparations revealed widespread trophozoites. The presence of double-dotted ring forms and banana-shaped gametocytes resulted in Plasmodium falciparum malaria being diagnosed. The patient was started treatment with oral artemether 20 mg/ lumefantrine 120 mg 2×4 tablets and trimethoprim-sulfamethoxazole. During his follow-up, hemoglobin levels regressed to 5.8 g/dL. The patient was diagnosed as having severe malaria. He visited our hematology unit, and exchange transfusion (EET) was recommended. Using an EET apheresis device, eight units of erythrocyte suspension was transfused. The cured patient was discharged. This case was found to be interesting and reminds us the possible presence of comorbid conditions associated with malaria in patients who have a history of travelling abroad. Although its effectiveness has not been proved thus far, as a striking result, EET was used as an alternative treatment in a patient with severe malaria.
Keywords: Adult; Africa South of the Sahara; Antimalarials; Artemisinins; Coinfection; Diagnosis, Differential; Erythrocyte Transfusion; Ethanolamines; Fluorenes; HIV Infections; Humans; Malaria, Falciparum; Male; Plasmodium falciparum; Severity of Illness Index; Travel; Turkey; antimalarial agent; artemether; artemisinin derivative; benflumetol; ethanolamine derivative; fluorene derivative; adult; Africa south of the Sahara; case report; complication; differential diagnosis; erythrocyte transfusion; human; Human immunodeficiency virus infection; isolation and purification; malaria falciparum; male; mixed infection; Plasmodium falciparum; severity of illness index; travel